Pengembangan Lingkungan Sekolah Sebagai Sumber Belajar untuk Mendukung Pembelajaran Berdiferensiasi di Sekolah Penyelenggara Pendidikan Inklusif - Hidayat Hidayat (Jurnal Didaktika Pendidikan Dasar, 2024)
Education serves to help students develop their potential, skills, and personal characteristics in a positive direction, both for themselves and their environment. But this has not been seen from the education in class VI at SDN Pulau Kelapa 02 Pagi, namely the lack of accommodation for participants with special needs to be able to learn optimally and also teachers have not used the school environment as a learning resource so that learning outcomes have not been optimal. The purpose of this study is to develop the school environment as a source of learning in schools providing inclusive education. Development research method with ADDIE method. Data collection techniques with observation, questionnaires, and learning outcomes tests. The research instruments used are observation sheets, interview guidelines, questionnaires, and learning outcomes tests with data analysis techniques are descriptive analysis. The results of development by utilizing the environment as a learning resource from the validation of media experts 98.5% of the category are very good, material experts 96.8% of the category is very good, pedagogic experts 96.6% of the category is very good. The level of practicalization by teachers obtained 96.5% results in the very good category and students obtained 95.5% results in the very good category. From the results of expert validation, it can be concluded that the development of the environment as a learning resource has a positive impact to support differentiated learning.